Nonparametric Analysis of Random Utility Models: Testing - Jörg Stoye; Yuichi Kitamura (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper aims at formulating econometric tools for investigating stochastic rationality, using the Random Utility Models (RUM) to deal with unobserved heterogeneity nonparametrically. Theoretical implications of the RUM have been studied in the literature, and in particular this paper utilizes the axiomatic treatment by McFadden and Richter (McFadden and Richter, 1991, McFadden, 2005). A set of econometric methods to test stochastic rationality given a cross-sectional data is developed. This also provides means to conduct policy analysis with minimal assumptions. In terms of econometric methodology, it offers a procedure to deal with nonstandard features implied by inequality restrictions. This might be of interest on its own right, both theoretically and practically.
Keywords: C14; C33; D12; 330